2009
DOI: 10.1002/jctb.2200
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective esterification of ibuprofen with ethanol as reactant and solvent catalyzed by immobilized lipase: experimental and molecular modeling aspects

Abstract: BACKGROUND: In recent years enantioselective esterification of racemic ibuprofen performed in organic co-solvent media such as isooctane and cyclohexane and catalyzed by lipases, has been proposed as an effective way to increase the concentration of S-ibuprofen in the racemic mixture. In this contribution, the enantioselective enzymatic esterification of (R,S)-ibuprofen with ethanol catalyzed by commercial Novozym 435 without the addition of a co-solvent is thoroughly investigated. Experimental data are furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…The substrates are heated to 70°C in order to melt the ibuprofen avoiding the use of a cosolvent for the dissolution of the reactants. More recently, our research group demonstrated that the esterification of ibuprofen using only ethanol as reactant and solvent yields 62% of ibuprofen conversion with an enantiomeric excess of 54% towards the S-isomer in 72 h of reaction [4]. C Following these previous findings, the present investigation shows preliminary results about the molecular interaction of ibuprofen and ethanol with Novozym Ò 435 in order to further understand the effect of the alcohol on the catalytic activity.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…The substrates are heated to 70°C in order to melt the ibuprofen avoiding the use of a cosolvent for the dissolution of the reactants. More recently, our research group demonstrated that the esterification of ibuprofen using only ethanol as reactant and solvent yields 62% of ibuprofen conversion with an enantiomeric excess of 54% towards the S-isomer in 72 h of reaction [4]. C Following these previous findings, the present investigation shows preliminary results about the molecular interaction of ibuprofen and ethanol with Novozym Ò 435 in order to further understand the effect of the alcohol on the catalytic activity.…”
Section: Introductionmentioning
confidence: 73%
“…Previous investigation on the stereo-selective esterification of racemic ibuprofen using ethanol as reactant and solvent (without additional cosolvents) demonstrated that Novozym Ò 435 deactivates after reusing it for four cycles of 48 h of reaction [4]. The conversion of ibuprofen and the enantiomeric excess towards the S-isomer obtained in that investigation are recalled in Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, Weis et al [16] have proposed a method for the enzymecatalyzed esterification or transesterification of triglycerides using emulsions as reaction medium. In contrast to other lipases, CALB has no lid covering the active site and show no interfacial activation [12,17], but a small ␣-helix domain located close to the active…”
Section: Introductionmentioning
confidence: 97%
“…Lipases from various origins have been studied with promising results in the esterification of profens, such as, lipase from Candida rugosa [8], Rhizomucor miehei [11], Candida antarctica [12]. C. antarctica lipase B (CALB), a globular protein with˛/ˇhydrolase fold, consists of 317 amino acids and its molecular weight is 33 kDa [13].…”
Section: Introductionmentioning
confidence: 99%